2008
DOI: 10.1021/np7007126
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Serratamolides and Diacyl Peptoglucosamine Derivatives from Serratia sp.

Abstract: The cyclodepsipeptide serratamolide A ( 1) and five closely related compounds together with three new glucosamine derivatives were isolated by bioactivity-guided chromatography from the XAD adsorber resin extract of a Serratia sp. The structures of the compounds were elucidated by 2D NMR and MS analyses. In addition to the known serratamolide A ( 1) with two C 10 alkyl chains, its derivatives always contained one C 10 chain combined with either C 12:1, C 12, C 11, C 9, or C 8 chains. The glucosamine derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 11 publications
8
44
0
Order By: Relevance
“…To unequivocally assign its molecular identity, we isolated the corresponding fraction by preparative HPLC and confirmed its structural identity by HR-MS and NMR analysis. All spectral data were in accordance with previous reports on serratamolide [29] (data not shown). Furthermore, the purified serratamolide was able to restore swarming activity to an swrW mutant strain, providing biological evidence that the purified compound is serratamolide (Fig 4C).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To unequivocally assign its molecular identity, we isolated the corresponding fraction by preparative HPLC and confirmed its structural identity by HR-MS and NMR analysis. All spectral data were in accordance with previous reports on serratamolide [29] (data not shown). Furthermore, the purified serratamolide was able to restore swarming activity to an swrW mutant strain, providing biological evidence that the purified compound is serratamolide (Fig 4C).…”
Section: Resultssupporting
confidence: 91%
“…Since the cAMP-CRP pathway is well known to regulate genes in response to the nutritional environment of the cell, this may indicate that serratamolide plays a role in a bacterium’s ability to acquire or compete for nutrients. Consistent with the role of serratamolide in competition, it has been shown that serratamolide has antimicrobial activity against both prokaryotes and fungi [22], [29], and that swarming motility, which requires biosurfactants such as serratamolide, confers resistance to antibiotics [30]. Another role for serratamolide was suggested by Barr-Ness and colleagues [31].…”
Section: Discussionmentioning
confidence: 70%
“…Prodigiosin has antibiotic properties [49] and is excreted from cells in extracellular vesicles [70]. Similarly, serratamolide has antimicrobial properties [33], [34] and is thought to be necessary for the generation of extracellular vesicles [70]. One possible function of PigP is to regulate production of antibiotics to compete for limited nutrients against other organisms, consistent with our observation that PigP is necessary to inhibit the growth of a gram-positive organism adjacent to S. marcescens colonies (Shanks, unpublished observations).…”
Section: Discussionsupporting
confidence: 82%
“…A recent study showed that serratamolide, originally characterized for its broad-spectrum antimicrobial activity [33], [34], can be a cytotoxic hemolysin [22]. Biosynthesis of serratamolide is catalyzed by the non-ribosomal peptide synthetase SwrW [20].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of chemically synthesized N-myristoyltyrosine and biologically produced N-acyltyrosine revealed similar surfactant properties although heterogeneity in the natural product was observed for fatty acids bound to tyrosine. Such promiscuity towards fatty acids with different chain lengths and saturation grades is common for biosurfactant synthesizing enzymes 24 62 and may result in the formation of mixed surface films or micelles with altered physical properties 63 . Hence, the here described N-acyl amino acids represent an interesting group of biosurfactants with a remarkably simple biosynthesis and a variety of important biotechnological applications.…”
Section: Discussionmentioning
confidence: 99%